Social Spending, Human Capital, and Growth in Developing Countries : Implications for Achieving the MDGs - Baldacci, Emanuele (IMF Working Papers; Working Paper ;, 2004)
Using panel data from 120 developing countries from 1975 to 2000, this paper explores the direct and indirect channels linking social spending, human capital, and growth in a system of equations. The paper finds that both education and health spending have a positive and significant direct impact on the accumulation of education and health capital, and thus can lead to higher economic growth. The paper also finds that other policy interventions, such as improving governance, reducing excessive budget deficits, and taming inflation, can also be helpful in moving countries toward the Millennium Development Goals (MDGs). As such, higher spending alone is not sufficient to achieve the MDGs.